Detection of oil palm haploids using stomata counting, flow cytometry, microsatellite and genomic in situ hybridization techniques - Zulkifili, Muhammad Azwan (2016)
Haploids are individuals with gametic chromosome (n) and valuable for breeding purposes such as to produce better hybrids and improve parental performances in hybrid combinations. Several methods were applied in order to screen haploid and doubled haploid plants such as stomata counting, flow cytometric analysis, microsatellite markers analysis and genomic in situ hybridization (GISH). However, the reliable method to screen for oil palm haploid and doubled haploid is yet to be reported. For ploidy level analysis, stomata counting was done by using ANNOVA but showed unreliable result due to factors such as atmosphere, water and disease. For homozygosity analysis, a hypodiploid, a mixed ploidy and two potential haploid seedlings were obtained via flow cytometry. These oil palm variants were screened with 15 microsatellite markers to determine the homozygosity. However, all samples were shown to be heterozygous. For characterization of parental genomes in intergeneric hybrids, sample used derived from wide hybridization technique which involved cross between four dura flowers with Cocos nucifera pollen. Then, GISH was carried out to characterize the parental genomes of these hybrids. The result showed the absence of signals from the hybrid chromosomes which mean that there was no Cocos nucifera genome introgressed into the hybrid. It may be due to the small proportion of Cocos nucifera. These hybrids then were further analysed using 16 specific coconut microsatellite markers. Two primers managed to exhibit the Cocos genome in all the samples. This proved that the microsatellite markers analysis was reliable to characterize the small proportion of Cocos nucifera genome in intergeneric hybrid. In conclusion, this study had showed that microsatellite analysis is the most reliable method to screen for haploid and doubled haploid oil palm.